Quality Management and Social Responsibility in the Context of Sustainable Development - Panait, Mirela; Marius Gabriel, Petrescu (Industrija, 2015)
The authors have analyzed two major determinants of sustainable development: quality management and social responsibility. The sustainable development is a concept used not only by researchers in domains like economics or ecology, but also by managers of different types of organizations that try to transpose this concept in real life. Many organizations like corporations, public institutions or small and medium enterprises promote the goals of sustainable development in their activity through various instruments like social responsibility`s programs or the use of different standards. So, the aim of this article is to analyze the relationship between quality management, social responsibility and sustainable development.
Keywords: Standards; Socialism; Responsibility; Sustainable development; Quality management